2014
DOI: 10.1111/oik.01279
|View full text |Cite
|
Sign up to set email alerts
|

Ecological communities are vulnerable to realistic extinction sequences

Abstract: Loss of species will directly change the structure and potentially the dynamics of ecological communities, which in turn may lead to additional species loss (secondary extinctions) due to direct and/or indirect effects (e.g. loss of resources or altered population dynamics). Furthermore, the vulnerability of food webs to repeated species loss is expected to be affected by food web topology, species interactions, as well as the order in which species go extinct. Species traits such as body size, abundance and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 54 publications
(119 reference statements)
4
48
2
Order By: Relevance
“…This could result in poor management advice and 70 undervaluation of the importance of biodiversity, because whilst relatively low levels of 71 biodiversity can be adequate to provide current function [12], higher levels might be needed 72 to support similar levels of function under environmental change [2,[13][14][15][16][17][18]. Therefore, 73 there is a need to identify the characteristics of resilient ecosystem functions and capture 74 these in both predictive models and management guidance. 75 76 Defining and applying the resilience concept 77 Resilience is a concept with numerous definitions in ecological [19], social [20] and other 78 sciences [21].…”
mentioning
confidence: 99%
“…This could result in poor management advice and 70 undervaluation of the importance of biodiversity, because whilst relatively low levels of 71 biodiversity can be adequate to provide current function [12], higher levels might be needed 72 to support similar levels of function under environmental change [2,[13][14][15][16][17][18]. Therefore, 73 there is a need to identify the characteristics of resilient ecosystem functions and capture 74 these in both predictive models and management guidance. 75 76 Defining and applying the resilience concept 77 Resilience is a concept with numerous definitions in ecological [19], social [20] and other 78 sciences [21].…”
mentioning
confidence: 99%
“…Food webs have been described as the defining objects of community ecology (Kitching 2004)-since if we want to understand fundamental issues such as (i) the extent to which populations of different taxa depend on each other, and how a change in the abundance of one species is likely to reflect into a change in the abundance of another (Polis and Winemiller 1996); (ii) how the extinction of one species may result in the extinction of another (Dunne et al 2002;Byrnes et al 2007;Srinivasan et al 2007;Pearse and Altermatt 2013;Berg et al 2015); (iii) how new species may infiltrate community structure and functioning (e.g., Henneman and Memmott 2001;Sheppard et al 2004;Byrnes et al 2007); or (iv) how community organization varies between different parts of the world (Lewinsohn and Roslin 2008;Forister et al 2015), among different feeding guilds (van Veen et al 2008;Novotny et al 2010) or with different levels of environmental change (Tylianakis et al 2007(Tylianakis et al , 2008; Tylianakis and Binzer 2014;Kaartinen and Roslin 2011), then we most certainly need to know who feeds on whom. Likewise, if we are interested in restoring a oncedisturbed habitat, then we should be asking whether we can restore not only what species are there, but also how they interact with each other (Montoya et al 2012).…”
Section: Food Webs As the Defining Objects Of Community Ecologymentioning
confidence: 99%
“…Using a dynamical approach and R 50 as a measure of food web robustness, Berg et al () showed, contrary to most previous studies (all using a topological approach, with one exception; Curtsdotter et al ), that top–down oriented primary species deletions (targeting species with high trophic position, large body size or low numerical abundance) can be as devastating as bottom–up oriented deletion sequences. This is of great relevance since much evidence (Lande , Cardillo et al ) suggests that species with high trophic position, large body size and/or low numerical abundance have disproportionally high extinction risks.…”
Section: Discussionmentioning
confidence: 91%